Fingerprints of a position-dependent Fermi velocity on scanning tunnelling spectra of strained graphene. (1st February 2018) - Oliva-Leyva, M; Barrios-Vargas, J E; Wang, Chumin
Abstract: Nonuniform strain in graphene induces a position dependence of the Fermi velocity, as recently demonstrated by scanning tunnelling spectroscopy experiments. In this work, we study the effects of a position-dependent Fermi velocity on the local density of states (LDOS) of strained graphene, with and without the presence of a uniform magnetic field. The variation of LDOS obtained from tight-binding calculations is successfully explained by analytical expressions derived within the Dirac approach. These expressions also rectify a rough Fermi velocity substitution used in the literature that neglects the strain-induced anisotropy. The reported analytical results could be useful for understanding the nonuniform strain effects on scanning tunnelling spectra of graphene, as well as when it is exposed to an external magnetic field.